2014
DOI: 10.2478/vzoo-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Status of Neoechinorhynchus Agilis (Acanthocephala, Neoechinorhynchidae), with a Description of two New Species of the Genus from the Atlantic and Pacific Mullets (Teleostei, Mugilidae)

Abstract: Taxonomic Status of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 6 publications
2
26
0
1
Order By: Relevance
“…But at a large scale, due to coastal nature of mullets, vicariance may explain the occurrence of a large portion of parasite species as, for example, in such widely distributed M. cephalus [43]. Current literature data of Dmitrieva et al [50], Sarabeev et al [17] and the present observations indicate that among the helminth fauna parasitizing this fish only one dactylogyrid monogeneans, Ligophorus chabaudi, was reported in both regions, while all other species of monogeneans, digeneans, acanthocephalans and nematodes occur only in the Mediterranean or in the Sea of Japan ( [8][9][10][11][12][13][14][15]17,18,33], the present study).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…But at a large scale, due to coastal nature of mullets, vicariance may explain the occurrence of a large portion of parasite species as, for example, in such widely distributed M. cephalus [43]. Current literature data of Dmitrieva et al [50], Sarabeev et al [17] and the present observations indicate that among the helminth fauna parasitizing this fish only one dactylogyrid monogeneans, Ligophorus chabaudi, was reported in both regions, while all other species of monogeneans, digeneans, acanthocephalans and nematodes occur only in the Mediterranean or in the Sea of Japan ( [8][9][10][11][12][13][14][15]17,18,33], the present study).…”
Section: Discussionmentioning
confidence: 72%
“…Identification of some metacercariae was done to genus or even family level (see Appendix A) due to the paucity of morphological features useful for the identification of larval stages and specific requirements for mounting and examination of specimens [20,30]. Identification of monogeneans followed Euzet and Combes [31] and Sarabeev et al [17], acanthocephalans followed Tkach et al [18] and nematodes followed Belous [32] and Orecchia and Paggi [33].…”
Section: Study Area Fish Sampling and Parasite Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acanthocephalan N. agilis is a widely spread parasite of grey mullets in the Atlantic and Pacific Oceans (Tkach, Sarabeev, & Shvetsova, ). This study showed that N. agilis penetrates with the proboscis in mucosal and submucosal layers and most likely induce an intense response of mucosal immunity in L. saliens and L. ramada (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Th e taxonomic status of Neoechinorhynchus agilis s. l. (Rudolphi, 1819) from grey mullets (Mugilidae) across localities in the North-East Atlantic and the North-West Pacifi c areas was recently reviewed by Tkach et al (2014). Th is taxonomic review performed on morphological features showed that there were three diff erent species of Neoechinorhynchus occurring in mullet hosts, two of those were recorded in the Atlantic and one in the Pacifi c waters (Neoechinorhynchus (Neoechinorhynchus) agilis (Rudolphi, 1819) and Neoechinorhynchus (Hebesoma) personatus Tkach, Sarabeev et Shvetsova, 2014, Neoechinorhynchus (Hebesoma) yamagutii Tkach, Sarabeev et Shvetsova, 2014, respectively).…”
Section: Introductionmentioning
confidence: 99%